"We Shall Be Better Canadians by Being Conscious Jews": Multiculturalism and the Construction of Canadian Identity in the Toronto Jewish Folk Choir - Wolters-Fredlund, Benita (Intersections, 2005)
Using the texts from concert programme notes, this paper describes the growing Canadian identity of Toronto Jewish Folk Choir during and after World War II. During this period the choir used rhetoric similar to what we would today call multiculturalism to argue for their place in Canadian culture. The choir's claims to Canadian identity are juxtaposed with colonialist and assimilationist attitudes toward culture at the time, demonstrating that through musical performance and discourse, the choir members were able to construct a positive Canadian identity for themselves despite their position as an ethnic minority outside the political mainstream.